A Different Construction for Some Classes of Quantum MDS Codes - Sari, Mustafa; Kolotoglu, Emre (SPRINGER BASEL AG, 2020)
Constructing quantum codes with large minimum distance plays a significant role in quantum computation and communication. Quantum maximum-distance separable (MDS) codes have important place among quantum codes since they are optimal with regard to the maximality of their minimum distances. In this paper, by making use of constacyclic codes over and Hermitian construction for quantum codes, we give different constructions for some classes of quantum MDS codes.
Keywords: Quantum MDS codes; Constacyclic codes; Cyclotomic cosets; DISTANCE; Mathematics